A study on clinico-pathological assessment of response to neoadjuvant chemotherapy in breast carcinoma - Mohapatra, Manisha; Sarma, Yerraguntla (Journal of cancer research and therapeutics, 2020)
Context: Neoadjuvant chemotherapy (NACT) has become a strategy in the multidisciplinary treatment approach to breast cancer. Since clinical and radiological responses do not correlate well with residual tumor after treatment, pathological evaluation of tumor response to chemotherapy is essential for accurate assessment. Aims: The aim of this study is to assess clinicopathological response to NACT in patients with invasive breast carcinoma. Settings and Design: Single institution, retrospective study was conducted for 4 years. Subjects and Methods: The study included 95 cases with the clinical diagnosis of locally advanced breast cancer and invasive breast carcinoma on histopathological examination of core needle biopsy/lumpectomy specimen. These cases were assessed for estrogen, progesterone, and human epidermal growth factor receptor 2 (HER2) receptors and treated with four cycles of NACT (adriamycin-cyclophosphamide) therapy. Histopathological examination of postchemo modified radical mastectomy specimens was performed following standard protocol. The pathological response of tumor to chemotherapy was assessed on Miller-Payne grading (MPG) and residual disease in breast and lymph node (RDBN) level. Statistical Analysis Used: Data were analyzed in percentages and presented in charts and tables. Results: Histopathological examination of pre-chemo biopsy specimens revealed invasive ductal carcinoma No special type (NST) in maximum, 89 (93.7%) cases. Majority 43 (45.3%) cases were HER2-positive followed by estrogen receptor-positive and/or progesterone receptor positive and HER2-positive type seen in 23 (24.2%) cases and 22 (23.1%) cases were triple negative. Sixteen (16.8%) and 76 (80%) cases showed pathological complete response (pCR) and partial pathological response, respectively, to NACT on MPG; 12 (12.6%) and 83 (87.4%) cases showed pCR and residual disease, respectively, on RDBN level. Majority 37.5% and 50% of cases showing pCR on MPG and RDBN level, respectively, were triple negative. Conclusions: This study highlights the clinicopathological response to NACT in carcinoma breast patients and identifies the molecular subtypes of these patients likely to respond to NACT.